STUDI KUALITATIF KONSEP TELECOMMUTING DI PERGURUAN TINGGI: PENGALAMAN PENGAJARAN DARING DOSEN DI MASA PANDEMI COVID-19 - Liswandi Liswandi (JURNAL LENTERA BISNIS, 2020)
The purpose of this qualitative research is to examine lecturers' understanding of how to experience telecommuting or working from home (WFH) through virtual or online teaching during the Covid-19 pandemic. Respondents for this study were 15 lecturers, who teach online from various private universities in Jakarta, Bogor, Tangerang and Bekasi (JABOTABEK). Semi-structured interviews via email and telephone were conducted using purposive sampling technique and content analysis approach. The results of this study illustrate that most of the lecturers (93%) understand the concept of telecommuting, the importance of information technology support and a home work environment to support their virtual or online teaching activities. The study also found several advantages of online teaching experiences such as flexibility, cost reduction and efficiency, work-life balance; and for the disadvantages, namely, lack of socialization for students and interaction between lecturers and students, and lack of infrastructure support, and the last is self-discipline.Keywords: Telecommuting, online teaching, flexibility.